Quality of Life in Internet Use Disorder Patients With and Without Comorbid Mental Disorders - Dieris-Hirche, Jan; te Wildt, Bert Theodor; Pape, Magdalena; Bottel, Laura; Steinbüchel, Toni; Kessler, Henrik; Herpertz, Stephan (Frontiers in Psychiatry, 2022)
Introduction Evidence from clinical studies on quality of life (QoL) in patients suffering from internet use disorders (IUD) is still limited. Furthermore, the impact of additional mental comorbidities on QoL in IUD patients has rarely been investigated yet. Materials and Methods In a cross-sectional clinical study 149 male subjects were analyzed for the presence and severity of an IUD as well as other mental disorders by experienced clinicians. The sample consisted of 60 IUD patients with and without comorbid mental disorders, 34 non-IUD patients with other mental disorders, and 55 healthy participants. Standardized clinical interviews (M.I.N.I. 6.0.0) and questionnaires on IUD symptom severity (s-IAT), QoL (WHOQOL-BREF), depression and anxiety symptoms (BDI-II and BAI), and general psychological symptoms (BSI) were used. Results Internet use disorder patients showed significantly reduced QoL compared to healthy controls (Cohen’s d = 1.64–1.97). Furthermore, IUD patients suffering from comorbid mental disorders showed significantly decreased levels of physical, social, and environmental QoL compared to IUD patients without any comorbidity (p < 0.05–0.001). Multiple linear regression analyses revealed that low levels of psychological, social and environmental QoL were mainly predicted by symptoms of depression. IUD factors were only significant predictors for the social and physical QoL. Discussion Internet use disorder patients with comorbid mental disorder reported the lowest QoL. Depression symptom severity was the most significant predictor of low QoL in IUD. Strategies to reduce depressive symptoms should therefore be considered in IUD treatment to increase patients’ QoL.